The social conscientious in the light of al-Hadith: A case study on University of Malaya's students / Hakim Harkati - Hakim , Harkati (2019)
Psychological studies are one of the most important needs of humanity in its daily life. The Western society has given it great importance, and has examined, developed and discovered its secrets. Among the findings reached at the end of the last century is emotional intelligence, which is based on knowing, controlling, managing and directing people's emotions for the benefit of the individual and society. The importance of this research lies in the fact that it will deal with the study of social emotional intelligence from an Islamic perspective and in the light of the Prophet's Hadith by selecting the Hadiths that refer to this subject and arranging them according to their topics, in order to reach emotional intelligence in an Islamic way,and then apply the results reached on a sample of students to see the extent of their application of the teachings of Islam in this area. The problem of research is that the emotional intelligence in the Islamic world is still based on translations in theory and is based on applied Western theory, which was originally curtailed to address the problems of Western society and its data of religion, culture, customs and traditions,which are largely incompatible with the Islamic society, as well as the lack of this science to the attention required from the Islamic perspective by individuals, associations and state institutions, and Islamic libraries do not publish much in this field. This research aims to contribute to the awakening of emotional intelligence through the Hadiths of the Prophet Muhammad -peace be upon him- and to highlight how He uses it in his daily life, and then apply those results to a sample of students of the University of Malaya to see their commitment to the teachings of the Islamic religion in this area. In this study, the researcher adopted the inductive method to follow the Hadiths and extract them from their sources, the analytical method to indicate the place of inference, using the comparative method when necessary and then the applied approach to the field study. One of the most important findings of the researcher that the Sunnah purified the subject of emotional intelligence in detail, which collected all the principles and objectives, and revoked some that is incompatible with human instinct and the will of the Creator. The Prophet's Sunnah also added the form of Lordliness and arbitration to the second source of legislation in the field of psychology, and came out of man, from pure individual interest, and from the obsession of happiness and success sought by the West in this world, to the satisfaction of God. The researcher also concluded that the Islamic community needs to return to the teachings of Islam in its emotional dealings to the hope of winning in the Here and Hereafter, taking into consideration the public interest, and the satisfaction of the Creator -the Almighty-.